PO148 Shortfall in mssn coverage in west essex associated with lack of specialist ms care for people with significant ms related morbidity – a service evaluation of ms care in west essex ccg. (1st December 2017) - Roelofs, Jacob; Whyte, Catriona; Gnanapavan, Sharmilee; Bowen, Amy; Mynors, Geraldine
Abstract : Introduction: Multiple Sclerosis (MS) is a neurological condition requiring multidisciplinary input to optimise patient outcomes. NICE recommends everyone with MS have regular reviews with an MSSN. 1, 2 The MS Society estimates a prevalence of 490 people with MS in West Essex served by a 0.8 WTE MS nurse, against the recommended caseload of 358 per whole time MS nurse. 3 Methods: In collaboration with the MS Trust GEMSS team, a survey was sent out to collect data on the quality of MS care. 265 patients where surveyed with 114 (43%) responses. Results: Of the 114 responders, 68.1% reported significant disability. 58% of patients had seen an MSSN in the last year compared to the GEMSS team average of 78%. 1 67% saw a neurologist, but 14% had not seen any healthcare professional about their MS. Patients who had not seen a MSSN in the last year reported significant MS-related morbidity. Discussion: 42% of patients had not seen an MSSN in the last year and reported significant MS-related morbidity including isolation, lack of confidence and medication anxiety. Additional MSSN input is needed to support these patients. References: Findings from the MS trust GEMSS MS specialist nurse evaluation project. Letchworth: MS Trust 2015. NICE quality standard MS 2016. Modelling sustainable caseloads for MSSN: Report on a consensus process led by the MS trust. British Journal of Neuroscience Nursing 2014;10(6):274–80.